High Levels of Sunflower Crushed in Diets for Feedlot Lambs Depress the Performance and Carcass Quality - Oliveira, E. R.; Gandra, J. R.; Moncao, F. P. [UNESP]; Gabriel, A. M. A.; Fernandes, A. R. M.; Goes, R. H. T.; Morais, M. G.; Muniz, E. B.; Pereira, T. L. (Islamic Azad Univ, Rasht, 2018)
This study aimed to evaluate the performance, some carcass characteristics from feedlot lambs receiving sunflower crushed (SC) in the diet on partial replacement of soybean meal. The experimental design was randomized block with four levels of SC in the diet (0, 10, 20 and 30% of dry matter (DM)). There was a linear reduction of 0.02; 0.003; 0.003 and 0.17% for each percentage unit of added SC in the diet, respectively, for the intake of dry matter, crude protein, daily weight gain and feed conversion ratio. There was a significant linear decrease of 0.15; 0.11 and 0.12% in slaughter weight, hot carcass and cold carcass, respectively, when increased 1% in the inclusion of SC in the diet. The use of SC did not influence the biological yield and characteristics of marbling, texture and color of the meat. The use of SC can be used in supplements for lambs in intensive production systems in partial replacement of soybean meal by up to 20%.
Keywords: carcass yield; co-products; marbling; performance; sunflower crushed